Inclusion of Ora-Pro-Nóbis (Pereskia aculeata) Leaf Meal in the Diet of Adult Nile Tilapia Improves Growth Performance and Intestinal Absorption Capacity Without Compromising Metabolic and Hematological Variables - Émerson J. A. Matos; Jailson Novodworski; Rafaela M. Gonçalves; Elisabeth C. Urbinati; Robie A. Bombardelli; Fábio Meurer (Veterinary Sciences)
Corn and soybeans are commodities and ingredients of global interest, whose prices fluctuate based on global demands. In this sense, this study aimed to assess ora-pro-nóbis (Pereskia aculeata) leaf meal (OLM) as an alternative to be included in the diets of Nile tilapia (Oreochromis niloticus). The optimal inclusion level of OLM in tilapia diets is investigated herein, aiming to improve their growth performance and health. Five diet variations containing OLM (0%, 5%, 10%, 15%, and 20%) were tested. Feed conversion and protein efficiency rates in the 5% and 10% OLM groups were statistically similar to the control group (p ≤ 0.05) and lower in the 15% and 20% OLM groups. Fish fed 5% and 10% OLM diets showed better feed efficiency, while higher OLM levels (15% and 20%) led to reduced carcass protein and ether extract levels. Increasing OLM levels enhanced intestinal villi height and area, associated with improved nutrient absorption and decreased liver fat degeneration, suggesting dietary adaptation and healthier liver conditions. Thus, OLM can be included up to 10% in tilapia diets, improving their growth performance, feed efficiency, and intestinal absorptive capacity without adversely affecting other parameters.